Freedom of Individual within the Domestic Sphere in an ‘A Family Man’: A Study: Examining the dissonance between familial expectations and personal freedom (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This play is an interesting study of the disastrous effects of family coercion true to his ideal of upholding the pride of the individual, Galsworthy, in his play, champions the value of personal freedom and opinion in the domestic sphere. It is an advocacy for greater tolerance and understanding for larger individual freedom in family surroundings.